Testing the Imperforate Anus Psychosocial Questionnaire (IAPSQ) on a Sample of Egyptian Children - Farraq, Shewikar; Abu Kassim, Noor Lide; Shehata, Sameh (Gavin Publishers, 2019)
Imperforate anus is a malformation of the anus, children with such type of congenital malformation usually undergo reconstructive surgery and be looked after by pediatric surgery nurses due to the problems with constipation and fecal incontinence after the colostomy is closed. Lack of control over bowels may affect a child’s psychosocial adjustment. The Aims of This Study are: (a) To evaluate the psychometric properties of the Arabic version of the Imperforate Anus Psychosocial Questionnaire (IAPSQ) on a sample of Egyptian children. (b) To assess the effect of (IA deformity, hypospadias, and rectal prolapse) on the psychosocial functioning of Egyptian children. (c) To compare the psychosocial functioning of children with congenital anomalies of the anus with those suffering from chronic diseases. Methodology: Subjects and Methods Study sample consisted of 35 children (with congenital anomalies of the anus) from Mansoura University Children’s Hospital (n=30), and Alexandria University Hospital (n=5), in Egypt. Data Collection: The data set of the current study was obtained within 3 months (from January to March 2017). Data Processing, Statistical Analysis and Results: Rasch analysis was used to evaluate the psychometric properties of the IAPSQ, as well as to generate the item difficulty and person ability measures. Analysis of the psychological dimension (23 items) gave a low person reliability (.37). With regard to the social dimension (12 items), the Rasch analysis showed a person reliability of .54. Comparisons between the Swedish Sample and the Egyptian Sample Psychological Domain: The Egyptian sample scored this item higher, indicating greater perceived concern by their mothers. it is more of a concerned for the Swedish sample compared to the Egyptian sample. Fathers are perceived by the Egyptian sample to be less loving and thinking more about their conditions compared to their mothers. Social Domain: Children distribution for this domain is also well spread out similar to the Swedish sample. Comparison between the two groups indicated that children with imperforate anus malformation has a higher quality of life (mean = 2.26 logits) compared to those children with chronic disease (mean = 1.78 logits). Reliability of measures is also higher for the study group (.76) compared to the comparison group (.41). The results of the DIF analysis showed that no significant DIF across the study and control groups